Microchanneled biomorphous Al2O3 coated with TiO2 aerogel for photocatalytic reduction of 4-nitrophenol - Bernardes, Joseane C.; Müller, Daliana; Latocheski, Eloah; Domingos, Josiel B.; Fey, Tobias; Rambo, Carlos R. (Ceramics International, 2022)
This work reports the preparation of rattan-derived biomorphic Al2O3 ceramics as supports for coating with TiO2 aerogels. The biomorphous Al2O3 samples were infiltrated with a TiO2-procusor sol, gelled and submitted to supercritical CO2 drying, which resulted in formation of a TiO2 aerogel layer on the channels’ walls. Subsequent thermal treatment at 450 °C led to the formation of anatase and rutile. The biomorphous Al2O3 was also coated with commercial TiO2 (Degussa P25) for comparison. Scanning electron microscopy revealed that the biomorphous Al2O3 maintained the original micro-anatomic features of rattan and the channels’ walls were coated with TiO2 aerogel particles. Coating with TiO2 aerogel increased the specific surface area and enhanced in 60% the photocatalytic efficiency in the reduction of 4-nitrophenol when compared with P25 coating. The microchanneled hierarchical structure of rattan-derived Al2O3 allowed fluid flow and the high surface area of TiO2 aerogels ensured adsorption of molecules during chemical reactions, which increased photocatalysis efficiency.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Biomorphous ceramics; Biotemplating; Photocatalysis; Rattan; TiO